2010
DOI: 10.1177/070674371005500502
|View full text |Cite
|
Sign up to set email alerts
|

Immigration and Suicidality in the Young

Abstract: W La Revue canadienne de psychiatrie, vol 55, no 5, mai 2010 274Objectives: Little research has focused on the relation of immigration and suicidal behaviour in youth. Nevertheless, the impact of migration on the mental health of youth is an issue of increasing societal importance. This review aimed to present studies on the prevalence of suicidal behaviour in immigrant youth in various countries and to provide possible explanations for suicidal behaviour in immigrant youth, especially regarding acculturation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 47 publications
2
36
0
2
Order By: Relevance
“…Rather, it is the interaction with other factors such as relationship with parents that plays a role in suicidal behavior among immigrant girls. Such suggestion was confirmed by Lipsicas [14]. When they found that familial problems were the most frequently reported factor for suicidal behavior among immigrant women.…”
Section: Introductionsupporting
confidence: 62%
See 2 more Smart Citations
“…Rather, it is the interaction with other factors such as relationship with parents that plays a role in suicidal behavior among immigrant girls. Such suggestion was confirmed by Lipsicas [14]. When they found that familial problems were the most frequently reported factor for suicidal behavior among immigrant women.…”
Section: Introductionsupporting
confidence: 62%
“…Female immigrants appear to be at a much higher risk for suicide attempt and suicidal ideation than male immigrants [25]. This was found in studies conducted in non-European countries as well [14]. What is of more interest is that female immigrants across countries relate their suicidality to familial problems.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…While research has showed that certain immigrant groups have a lower risk of suicide behaviors than the majority population [6,7,9], our results agreed with certain studies which have found that immigrant adolescents had a higher risk and that poor family environment, lack of parental support, not living with both parents, substance use, physical and sexual abuse, and poor mental health play strong confounding roles [6,10,11,20,48,49]. Some studies reported that the risk of suicide ideation was higher among adolescents who have family problems or difficulties in relationships with parents [6,8,9,11,48,49]. The children of immigrants often reach a higher level of acculturation and education than their parents, contributing to intergenerational conflict, decreased understanding, and closeness between children and parents [6,50].…”
Section: Discussionsupporting
confidence: 89%
“…The literature is abundant for adults but rather scarce for adolescents. According to a review of literature, little research has focused on suicide behaviors in immigrant youth, most research does not differentiate ethnic minorities, and the risk of suicide behaviors varies by ethnicity and country of settlement [8]. The available studies have reported that various immigrant groups can be at an increased or lower risk of suicide behaviors than the majority population [6,7,9].…”
Section: Introductionmentioning
confidence: 99%